An Early Diagnostic Clue for COL18A1- and LAMA1-Associated Diseases: High Myopia With Alopecia Areata in the Cranial Midline - Wang, Panfeng; Jia, Xiaoyun; Xiao, Xueshan; Li, Shiqiang; Long, Yuxi; Liu, Mengchu; Li, Yongyu; Li, Jun; Xu, Yan; Zhang, Qingjiong (Frontiers in Cell and Developmental Biology, 2021)
Background: High myopia with alopecia areata in the occipital region has been observed in patients with Knobloch syndrome caused by COL18A1 mutations. This study investigated other possible genetic causes of high myopia in patients with alopecia areata in the cranial midline. Methods: Six patients with early onset-high myopia and alopecia areata in the cranial midline were recruited. Targeted high-throughput sequencing was performed on the proband’s DNA to detect potential pathogenic variants. Cosegregation analysis was performed for available family members. Minigene assay and RNA Sequencing were used to validate the abnormality possible splicing change and gross deletion. Ophthalmological and neuroimaging examinations were performed. Results: Eight novel and one known loss-of-function mutants was detected in all six patients, including three homozygous COL18A1 mutations in three patients with scalp leisure in the occipital region; and one homozygous as well as two compound-heterozygous LAMA1 mutations in three patients with scalp leisure in the parietal region. Further assessments indicated that patients with COL18A1 mutations had Knobloch syndrome, and the patients with LAMA1 mutations had Poretti-Boltshauser syndrome. Conclusions: Our study found that early-onset high myopia with midline alopecia areata could be cause not only by mutations of COL18A1 gene but also by mutations in the LAMA1 gene. To our knowledge, we are the first to observe scalp defects in patients with LAMA1 mutations. High myopia with alopecia areata in the cranial midline could be treated as an early diagnostic clue for ophthalmologists to consider the two kinds of rare diseases.